1985
DOI: 10.1111/j.1365-2265.1985.tb00145.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vasopressin Infusion on Glucose Metabolism in Man

Abstract: Studies on intact animals and isolated rat hepatocytes have shown that arginine vasopression (AVP) stimulates glycogen phosphorylase to break down glycogen and raise plasma glucose concentrations. Since no similar work has been performed on healthy human adults, the effect of moderate (25 pmol/min) and high (75 pmol/min) dose AVP infusion on plasma glucose, intermediary metabolites, glucose kinetics, and circulating glucagon and insulin concentrations was investigated. After AVP infusion, plasma glucose rose f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 24 publications
4
66
1
Order By: Relevance
“…An increasing body of data suggests that VP may play a part in glucose homeostasis, besides its well-defined role in urine concentration and body water homeostasis. Acute VP infusion in the rat and in healthy individuals was shown to induce a transient rise in blood glucose concentration [4][5][6]. Ex vivo studies showed that VP stimulates gluconeogenesis and glycogenolysis through the activation of hepatic arginine VP receptor 1A (V1aR), and the release of either glucagon or insulin, depending on concomitant extracellular glucose levels, through the activation of arginine vasopressin receptor 1B (V1bR) in pancreatic islets [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of data suggests that VP may play a part in glucose homeostasis, besides its well-defined role in urine concentration and body water homeostasis. Acute VP infusion in the rat and in healthy individuals was shown to induce a transient rise in blood glucose concentration [4][5][6]. Ex vivo studies showed that VP stimulates gluconeogenesis and glycogenolysis through the activation of hepatic arginine VP receptor 1A (V1aR), and the release of either glucagon or insulin, depending on concomitant extracellular glucose levels, through the activation of arginine vasopressin receptor 1B (V1bR) in pancreatic islets [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…AVP levels are markedly increased in patients with poorly controlled diabetes mellitus [8] and AVP infusion leads to increased blood glucose levels in healthy subjects [9]. AVP predicts diabetes mellitus independently of a broad range of established diabetes risk factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the first possible mechanism, the central AVP/V1a receptor signal in the CNS regulates hepatic glucose production. AVP administration into the NTS or cisterna magna induced hyperglycemia (347,464,542). It has also been reported that AVP stimulates GABAergic neurons in vitro (214) and that GABAergic neurons suppress hepatic glucose production (259).…”
Section: V1a Receptor and Glucose Homeostasismentioning
confidence: 99%